Asymptotic behavior of solutions for differential equations with double singularity in conditionally stable case - Karandzhulov, L.I. (Нелінійні коливання, 2018)
The double singular perturbation for boundary-value problem for nonlinear system of ordinary differential equations is considered. For a formal asymptotic solution, constructed by the method of boundary
functions and generalized inverse matrices and projectors, we prove an asymptotic property of the formal
series. Розглянуто подвiйно сингулярне збурення граничної задачi для нелiнiйної системи звичайних
диференцiальних рiвнянь. Для формального асимптотичного розв’язку, який побудовано за методом граничних функцiй та узагальнених обернених матриць i проекторiв, доведено асимптотичну властивiсть формального ряду.